Penggunaan guano dan pupuk NPK Mutiara untuk memperbaiki kualitas media subsoil dan pertumbuhan bibit kelapa sawit (Elaeis guineensis Jacq.) - Mukhtaruddin Mukhtaruddin; Sufardi Sufardi; Ashabul Anhar (Jurnal Floratek, 2015)
Use of Guano and Fertilizer NPK to Improve Quality of Subsoil Media and Growth of Oil Palm SeedlingABSTRACT. Utilization of subsoil as a growing medium for the nursery is a challenge to replace the role of topsoil as media for oil palm nurseries mainly on main nursery. This research was aimed at studying the effects of organic Guano and inorganic NPK fertilizer on oil palm seedling growth on sub soil growing media. The experiment was conducted in a pot, arranged in a randomized complete block design (RCBD), factorial 4x3 with 3 replicates. There were two factors examined, 1) guano dose consisting of four levels, namely: 0 kg, 0.5 kg, 1.0 kg and 1.5 kg/polybags and 2) inorganic fertilizers NPK consisting of three levels, namely: 0, 15, and 30 g/polybags. The results showed that subsoil can be used for growing media with applications of fertilizer Guano and inorganic NPK fertilizer. Guano and NPK fertilizer affected several soil chemical properties, i.e. increase in soil pH, available total C and N and P, and cation exchange capacity (CEC) and affected growth of oil palm seedling at age 16 weeks after planting. The best combination for the best seedling growth was obtained at 1.5 kg Guano + 30 kg NPK